2022
DOI: 10.1038/s41598-022-09056-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic serum abnormalities in dogs with hepatopathies

Abstract: Hepatopathies can cause major metabolic abnormalities in humans and animals. This study examined differences in serum metabolomic parameters and patterns in left-over serum samples from dogs with either congenital portosystemic shunts (cPSS, n = 24) or high serum liver enzyme activities (HLEA, n = 25) compared to control dogs (n = 64). A validated targeted proton nuclear magnetic resonance spectroscopy platform was used to assess 123 parameters. Principal component analysis of the serum metabolome demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 92 publications
(127 reference statements)
0
10
0
2
Order By: Relevance
“…However, the ranges of ages in each group were broad and overlapping. In a simultaneously performed study on canine hepatopathies, we showed that there were no significant differences in serum concentrations of the metabolomics data between younger and older adult control dogs (expect citrate concentrations, p = 0.049) [20]. The serum samples of the CONT group used in this study were also part of the control group in this recent study on canine hepatopathies [20].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, the ranges of ages in each group were broad and overlapping. In a simultaneously performed study on canine hepatopathies, we showed that there were no significant differences in serum concentrations of the metabolomics data between younger and older adult control dogs (expect citrate concentrations, p = 0.049) [20]. The serum samples of the CONT group used in this study were also part of the control group in this recent study on canine hepatopathies [20].…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, 11 relative concentrations of fatty acids and seven selected amino acid ratios were calculated. The resulting 123 metabolic parameters were also documented in our recent study of canine hepatopathies [20]. Medians for all parameters of the CONT group fell in the previously established serum reference intervals for dogs of all ages [19].…”
Section: Metabolomic Analysesmentioning
confidence: 71%
“…GlycA is a composite inflammatory marker elevated in multiple chronic diseases in humans, and is associated with chronic low-grade inflammation, risk of severe infection, diabetes mellitus, and even mortality (Ahola-Olli et al, 2019;Würtz et al, 2017). Until now, it has been scarcely studied in dogs, but elevated concentrations have been observed in dogs with hypo-and hyperadrenocorticism, elevated liver enzyme activities, hyperlipidemia and phenobarbital treatment (Imbery et al, 2022a(Imbery et al, , 2022bOttka et al 2021aOttka et al , 2021b.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, results of glucose and lactate should be interpreted with caution. However, the use of the leftover samples and comparison with well-established markers is still an excellent, animal-friendly resource for new insights and hypothesis generation (Imbery et al, 2022a(Imbery et al, , 2022bOttka et al, 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, neoplastic diseases investigated through omics technologies are hematopoietic neoplasms [79][80][81][82], mammary tumors [83][84][85], oral neoplasms [86], neuroendocrine tumors [87], and melanocytic tumors [73,88]. Further disorders addressed by omics approaches include cardiopathies [89][90][91], endocrinopathies such as hyperadrenocorticism [92] and diabetes mellitus [93,94], hepatopathies [95][96][97], chronic kidney disease [98,99], and inflammatory/infectious diseases(i.e., sepsis [100], pyometra [101], and vector-borne diseases [102,103]). Interestingly, using omics approaches, great attention has also been paid to the gut microbiota [104,105] and dietary regimens [106,107].…”
Section: Integrative Multiomics Approaches In Veterinary Medicinementioning
confidence: 99%